Growth of massive cementite layers; thermodynamic parameters and kinetics - Nikolussi, Marc (J Mater Sci, 2009)
Massive, pure cementite layers were grown on ferrite substrates by nitrocarburising in a dedicated NH(3)/H(2)/CO/N(2) containing gas atmosphere at temperatures in the range of 783–843 K. From the parabolic layer-growth constants, an “apparent” activation energy for cementite-layer growth of 109 ± 12 kJ/mol was obtained. This “apparent” activation energy can be subdivided into a positive contribution due to the activation energy for (tracer) diffusion of carbon in cementite and a negative contribution due to the temperature dependence of the difference of the carbon activity in cementite at the surface and at the interface cementite/ferrite.